2020
DOI: 10.3389/fimmu.2020.01218
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of Immune Cell Infiltration Identifies a Prognostic Immune-Cell Characteristic Score (ICCS) in Lung Adenocarcinoma

Abstract: Background: The tumor microenvironment (TME) consists of heterogeneous cell populations, including malignant cells and nonmalignant cells that support tumor proliferation, invasion, and metastasis through extensive cross talk. The intra-tumor immune landscape is a critical factor influencing patient survival and response to immunotherapy. Methods: Gene expression data were downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus databases. Immune cell infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(137 citation statements)
references
References 46 publications
8
127
2
Order By: Relevance
“…The immune cell infiltration status was acquired based on quanTIseq, a method to quantify the fractions of 10 immune cell types from bulk RNA-sequencing data (Finotello et al, 2019 ), by using the single-sample gene set enrichment approach (Zuo et al, 2020 ) to the transcriptomes of HCC.…”
Section: Methodsmentioning
confidence: 99%
“…The immune cell infiltration status was acquired based on quanTIseq, a method to quantify the fractions of 10 immune cell types from bulk RNA-sequencing data (Finotello et al, 2019 ), by using the single-sample gene set enrichment approach (Zuo et al, 2020 ) to the transcriptomes of HCC.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, it also suggested that the vitamin-related risk signature can directly predict the local immune status of glioma, highlighting its strong predictive ability. It has been shown that higher immune cells in ltration indicates a worse outcome in both LGG and GBM (36). This further con rmed the accuracy and reliability of the vitamin-related risk signature in predicting the local immune response of the glioma microenvironment and the prognosis of glioma patients.…”
Section: Immune Features Of the Low-and High-risk Groupsmentioning
confidence: 59%
“…Figure 3F show the relationship between the enrichment of these six types of immune cells and the expression level of ITGA3 in TCGA, CGGA, and GSE16011 datasets. It had been con rmed that high immune cell in ltration resulted in a more unfavorable prognosis in glioma (27). These results indicated that ITGA3 reduced the purity of glioma by promoting the enrichment of immune cells in the glioma microenvironment, thereby affecting the prognosis of glioma.…”
Section: Relationship Between Itga3 and Tumor Purity Of Gliomamentioning
confidence: 92%